2022
DOI: 10.1186/s12966-022-01262-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of excise tax on sugar-sweetened beverages in Catalonia, Spain, three and a half years after its introduction

Abstract: Background The World Health Organisation urges countries to levy specific excise taxes on SSBs. Currently, more than 50 countries have introduced some type of tax on SSBs. In March 2017, the Autonomous Region of Catalonia approved the introduction of a tiered excise tax on SSBs for public health reasons. To evaluate the effect of the Catalonian excise tax on the price and purchase of sugar-sweetened beverages (SSBs) and their possible substitutes, i.e., non-sugar-sweetened beverages (NSSBs) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 47 publications
(49 reference statements)
1
4
0
1
Order By: Relevance
“…In addition, the two-way deterministic sensitivity analysis revealed that the price effect is greatest at higher tax and pass-on rates. In comparison with other studies, overall, the results are supportively similar to those found in other studies concluding the efficacy of sugar tax in reducing the consumption of SSB see Hangoma, et al, 2020;Manyema, et al, 2014;Nakhimovsky, et al, 2016;Nor, et al, 2021;Royo Bordonada, et al, 2022). However, the magnitude of the impact on consumption varies across different countries and regions.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, the two-way deterministic sensitivity analysis revealed that the price effect is greatest at higher tax and pass-on rates. In comparison with other studies, overall, the results are supportively similar to those found in other studies concluding the efficacy of sugar tax in reducing the consumption of SSB see Hangoma, et al, 2020;Manyema, et al, 2014;Nakhimovsky, et al, 2016;Nor, et al, 2021;Royo Bordonada, et al, 2022). However, the magnitude of the impact on consumption varies across different countries and regions.…”
Section: Discussionsupporting
confidence: 89%
“…However, it should be noted that, similar to other substances (e.g. tobacco, alcohol, sugary beverages), environmental prevention based on law restrictions can have a significant impact on reducing drug demand [246][247][248]. Specifically, the following measures could be conducted: (1) increasing the price of ED; (2) establishing minimum-age laws to purchase these beverages (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Concretamente en España se han promulgado distintas acciones regulatorias dirigidas a restringir el consumo de tabaco en espacios públicos (Ley 28/2005 y Ley 42/2010), y otras dirigidas al control de los alimentos, como el impuesto sobre las bebidas azucaradas (Decreto Ley 13/2019) o el sistema de etiquetado (Real Decreto 1412/2018). Estas medidas regulatorias basadas en la EC han demostrado tener un impacto significativo sobre la salud de las personas, en términos de consumo de tabaco, exposición al humo ambiental del tabaco o morbilidad asociada (Unidad de Prevención del Tabaquismo, 2016, 2020), así como en la reducción del consumo de bebidas azucaradas (Royo-Bordonada et al, 2022). De forma complementaria, se han promovido intervenciones preventivas basadas en la trasmisión de información veraz sobre distintas conductas de salud, con el fin de deshacer los mitos y sesgos cognitivos relacionados con distintas conductas y aumentar la percepción de riesgo o proporcionar habilidades sociales que mejoran la toma de decisiones (Delegación del Gobierno para el Plan Nacional sobre Drogas, 2022).…”
Section: Economía Conductual Y Salud Públicaunclassified